Nicaragua: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2023)
The IDB-funded PFPAS program has provided an important financial injection into Nicaragua’s agricultural research system during 2013–2018. The program has made important strides in rehabilitating some of INTA’s run-down research infrastructure, in offering degree and short-term training to research staff, and in strengthening linkages between agricultural research and producers. Notwithstanding the important achievements of PFPAS, Nicaragua’s agricultural R&D investment levels remain too low to provide the necessary technological solutions to enhance agricultural productivity and reduce rural poverty. As of 2020, the country invested just 0.22 percent of its agricultural GDP in agricultural research, which is insufficient to effectively address the many challenges the agricultural sector is facing. Nicaragua lacks a critical mass of highly qualified agricultural researchers. Building on the achievements of PFPAS, continued and accelerated training of young researchers to the MSc and PhD level remains critical. In addition, local university programs in agricultural sciences need to be strengthened so that more scientists have the opportunity to pursue higher level degrees in-country.